Haiti : Joint Staff Advisory Note of the Poverty Reduction Strategy Paper. (IMF Staff Country Reports; Country Report ;, 2008)
A key challenge of the macroeconomic program is to increase domestic revenue mobilization to help support the higher levels of public spending for investment and basic services. For the current fiscal year, the authorities are developing a supplemental budget to reprogram existing budgetary resources in line with identified poverty reduction strategy priorities. The section on democratic governance presents a forthright analysis and detailed reform program for the justice and security sectors. Private investment in tourism will require improvements in the security situation.